A one-step specific assay for continuous detection of sirtuin 2 activity - Qi Dai; Zhihua Zheng; Fan Xia; Peiqing Liu; Min Li (Elsevier, 2019)
Sirtuins (SIRTs) are nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylases with diverse physiological functions. A variety of small molecules have been developed to interrogate the physiological function of SIRTs. Therefore, it is desirable to establish efficient and convenient assays to screen SIRTs modulators. In this study, we designed a series of fluorescent nonapeptide probes derived from substrates of SIRT1-SIRT3. Fluorescence increment of these probes is based on SIRT-mediated removal of the acyl side chain with fluorophore, which makes this system free of lysine-recognizing protease. Comparing the reaction of these fluorescent nonapeptide substrates with SIRT1-SIRT3 and SIRT6, it was confirmed that this assessment system was the most suitable for SIRT2 activity detection. Thus, SIRT2 was used to modify substrates by truncating the amino acids or lysine side chain of nonapeptide. Finally, two specific and efficient fluorescent probes for SIRT2, ne-D9 and ne-K4a, were developed. Evaluation of the results revealed that ne-K4a based assay was more suitable for modulators screening in vitro, while the other specific substrate ne-D9 was stable in cell lysate and could detect the activity of SIRT2 in the same. In summary, this study presents a novel strategy for detecting SIRT2 activity in vitro and in cell lysate. Key words: Deacetylate, Deacylate, Fluorescent probe, One-step assay, Sirtuins, SIRT2